Identification of an immune‐related gene signature as a prognostic target and the immune microenvironment for adrenocortical carcinoma. Issue 9 (17th August 2022) - Xu, Chengdang; Qin, Caipeng; Jian, Jingang; Peng, Yun; Wang, Xinan; Chen, Xi; Wu, Denglong; Song, Yuxuan
Abstract: Background: Adrenocortical carcinoma (ACC) is a rare endocrine malignancy. Even with complete tumor resection and adjuvant therapies, the prognosis of patients with ACC remains unsatisfactory. In the microtumor environment, the impact of a disordered immune system and abnormal immune responses is enormous. To improve treatment, novel prognostic predictors and treatment targets for ACC need to be identified. Hence, credible prognostic biomarkers of immune‐associated genes (IRGs) should be explored and developed. Material and methods: We downloaded RNA‐sequencing data and clinical data from The Cancer Genome Atlas (TCGA) data set, Genotype‐Tissue Expression data set, and Gene Expression Omnibus data set. Gene set enrichment analysis (GSEA) was applied to reveal the potential functions of differentially expressed genes. Results: GSEA indicated an association between ACC and immune‐related functions. We obtained 332 IRGs and constructed a prognostic signature on the strength of 3 IRGs ( INHBA, HELLS, and HDAC4 ) in the training cohort. The high‐risk group had significantly poorer overall survival than the low‐risk group ( p < .001). Multivariate Cox regression was performed with the signature as an independent prognostic indicator for ACC. The testing cohort and the entire TCGA ACC cohort were utilized to validate these findings. Moreover, external validation was conducted in the GSE10927 and GSE19750 cohorts. The tumor‐infiltrating immune cells analysis indicated that the quantity of T cells, natural killer cells, macrophage cells, myeloid dendritic cells, and mast cells in the immune microenvironment differed between the low‐risk and high‐risk groups. Conclusion: Our three‐IRG prognostic signature and the three IRGs can be used as prognostic indicators and potential immunotherapeutic targets for ACC. Inhibitors of the three novel IRGs might activate immune cells and play a synergistic role in combination therapy with immunotherapy for ACC in the future. Abstract : In the present study, we aimed to identify an immune‐related gene (IRG) prognostic signature and find potential immunotherapeutic targets for adrenocortical carcinoma (ACC) patients. In addition, what we found is that three‐IRG prognostic signature and the three IRGs could serve as prognostic indicators and potential immunotherapeutic targets for ACC.